USE OF PEDAGOGICAL SITUATIONS ON FOREIGN LANGUAGE CLASSES IN HIGHER EDUCATION (Pedagogy of Higher and Secondary Education, 2022)
The article studies the notion of "pedagogical situation". It presents the types of pedagogical situations at foreign language lessons.